Past, current, and future willingness to engage with treatment targets: Applying user‐centered design to inform the design of a mobile behavioral intervention. Issue 4 (29th February 2020) - Weinheimer, Emilie A.; Chang, Angela; Neubert, Sarah W.; Wildes, Jennifer E.; Graham, Andrea K.
Abstract: Objective: User‐centered design can improve engagement with and the potential efficacy of behavioral interventions, but is underutilized in health care. This work demonstrates how design methodologies can inform the design of a mobile behavioral intervention for binge eating and obesity. Method: A needs assessment was conducted with end‐users ( N = 22 adults with obesity and recurrent binge eating [≥12 episodes in 3 months] who were interested in losing weight and addressing binge eating), which included assessing participants' past/current and future willingness to engage with 20 treatment targets for managing binge eating and weight. Targets focused on improving dietary intake, increasing physical activity, and reducing overvaluation of weight and/or shape, unhealthy weight control practices, and negative affect. Results: Participants' past and current use of targets varied. For all targets except those addressing unhealthy weight control practices, on average, participants had increasing levels of willingness to try targets. Among participants not currently using a target, at least some were willing to use every target again. Discussion: Findings inform ways to personalize how users begin treatment. Furthermore, this study exemplifies how user‐centered design can inform ways to ensure that digital interventions are designed to meet end‐users' needs to improve engagement and clinical impact.